Pengembangan Media Pembelajaran Aplikasi Ular Tangga Berbasis Digital pada Pembelajaran IPAS Kelas V Sekolah Dasar - Kinanti Paramuditha, Elvin; Hakim, Lukman; Sri Nindiati, Dina (Papanda Publisher, 2025)
This study aims to develop a digital-based learning media in the form of a snakes and ladders application for the Social and Natural Sciences (IPAS) subject, specifically on the topic of